Seasonal trends in abundance and composition of marine debris in selected public beaches in Peninsular Malaysia - Julyus Melvin, Mobilik; Teck-Yee, Ling; Mohd Lokman, Bin Husain; Ruhana, Hassan (American Institute of Physics Inc, 2015)
The abundance and composition of marine debris were investigated at Saujana (in the state of Negeri Sembilan) and Batu Rakit (in the state of Terengganu) beaches during surveys conducted in December 2012 (northeast monsoon), May 2013 (intermediate monsoon) and July 2013 (southwest monsoon). A total of 4,682 items of debris weighing 231.4 kg were collected and sorted. Batu Rakit received substantially greater quantities of debris (815±717 items/km or 40.4±13.0 kg/km) compared to Saujana (745±444 items/km or 36.7±18.0 kg/km). Total debris item was more abundant during the southwest monsoon (SWM) (1,122±737 items/km) compared to the northeast monsoon (NEM) (825±593 items/ km) and the intermediate monsoon (IM) (394±4 items/km) seasons. Plastic category (88%) was the most numerous items collected and object items contributed 44.18% includes packaging, plastic fragments, cups, plastic shopping bags, plastic food wrapper, clear plastic bottles from the total debris items collected. Object items associated with common source (47%) were the highest debris accumulated, followed by terrestrial (30%) and marine (23%) sources. The high percentage of common and terrestrial sources during SWM season requires immediate action by marine environment stakeholders to develop and introduce strategies to reduce if not totally eliminates the marine debris in the marine environment. Awareness should be continued and focused on beach users and vessels' crew to alert them on the alarming accumulation rate of marine debris and its pathways into the marine environment.